It's Too Darn Hot: How Rising Temperatures are Linked to Climate Change in the U.S. Print Media - Byrum, Betsy. (2017)
Abstract: The print media has a profound impact on the public's opinion and knowledge of environmental issues, including climate change. This thesis explores how the media connects a key impact of climate change, rising temperatures, to climate change itself through a content analysis of newspaper articles about rising temperatures from the New York Times, USA Today, the Wall Street Journal, and the Washington Post from January 1, 1988 to December 31, 2015. This analysis finds that while a vast majority of articles about rising temperatures mentioned climate change and/or global warming, articles' discussions of these issues lacked depth, and fewer than half mentioned other impacts of climate change and other political, social, and economic issues. In one of the most striking findings of this study, it was discovered that few articles about rising temperatures discussed the social impacts of climate change, including social justice, political unrest, and impacts to vulnerable populations.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Julian Agyeman.; Keywords: Climate change, and Mass communication.